(untitled) (BIRDEM Medical Journal, 2017)
Background: This study was designed to assess the effectiveness of use of the fracture risk assessment system (FRAX) as risk assessment tool for osteoporosis risk score scale in Bangladeshi subjects and to assess how the results of the tools correlate with each other. Methods: This cross-sectional study was conducted between January 2016 to August 2016. The study population was randomly collected 600 Bangladeshi subjects; who attended outpatient department (OPD) of MARKS Medical College & Hospital, Dhaka, Bangladesh. The age range of the subjects was between 40 to 75 years. The subjects had not done a bone mineral density (BMD) score. None of them were previously diagnosed or got treatment for osteoporosis. A questionnaire was designed to complete the osteoporosis specific risk score sheet. Major osteoporotic and hip fracture incidence to 10-years as a function of the FRAX probability was calculated by using fracture risk assessment system. Results: A total of 600 subjects were included. Among them, 59.2% and 40.8%were male and female respectively. Mean age (Mean ± SD) of the study, subjects were 52.16±7.96 years. Among study subjects, mean BMI was more in females in comparison to males (p<0.05). The FRAX predicted 10-year risk assessment scores of major osteoporotic fractures were significantly more in females than males (p<0.02). Risk assessment scores of both major osteoporotic fractures and hip fractures showed significant association in post-menopausal women when compared with there who were not menopausal (p<0.05). Risk assessment factors for risk scores did differ significantly among male and female subjects and among postmenopausal and non-menopausal women. Among risk assessment factors, subjects having finally history of fracture hip, glucocorticoids, rheumatoid arthritis showed strong association with presence of ≥20% risk scores for major osteoporotic fracture (p<0.05) and ≥ 3% for hip fracture (p<0.05). Subjects having history of previous fracture and secondary osteoporosis showed only significant association with ≥3% risk scores for hip fracture (p<0.05). Conclusion: The public health burden of fractures will fail to compromise unless the subset of patients who are at increased risk for fracture are identified and treated. Ten-year fracture risk assessment with the fracture risk assessment system is increasingly used to guide for treatment decisions. It is an effective tool to predict fracture probability, particularly in developing countries like Bangladesh, where most of the patients cannot afford expensive dual energy x-ray absorptiometry scans. Birdem Med J 2018; 8(1): 9-15